Plant extract as a strategy for the management of seed pathogens: a critical review (Research, Society and Development, 2021)
Abstract Seeds associated to fungal pathogens are efficient vehicles for disease dissemination in the field. Such pathogens affect the seed quality and longevity, causing a decrease or loss of germination, discoloration, necrosis, and decay, in addition to leading to the production of mycotoxins in some pathosystems. To control them several synthetic chemicals are used. Nevertheless, the use of synthetic chemicals poses a risk to human health and the environment. Therefore, there is a growing demand for the use of alternative methods for the treatment of seeds, such as plant extracts. This review evaluated the use and efficacy of plant extracts for the control of fungal pathogens associated to seeds. Some control methods are used in seed treatment, plant extracts stand out due to the secondary metabolic in their constitution, which inhibit pathogen growth. The literature review showed that 100% of the studies reported that plant extracts were efficient to control the different pathogens evaluated, 63% stated an increase in seed germination, 21% reported no change in germination, 5% mentioned negative interference, and 11% did not evaluate the use of plant extracts. The aqueous extracts were used as extractors in 72% of the studies. Plant extracts were reported as promising to replace synthetic fungicides in 33% of the studies; however, 67% did not compare their use. Nevertheless, efficient extraction methods are required, considering low persistence and volatilization of plant extracts in the field. Plant extracts are efficient to control fungal pathogens.